Signet‐ring cell/histiocytoid carcinoma in the axilla: A case report with genetic analysis using next‐generation sequencing. (30th September 2020) - Ito, Yui; Ishida, Mitsuaki; Ohe, Chisato; Miyasaka, Chika; Tsuta, Koji
Abstract: Signet‐ring cell/histiocytoid carcinoma (SRCHC) is a very rare skin appendage cancer, with an extremely rare occurrence in the axilla. This study describes the 11th case of SRCHC occurring in the axilla and reports the first gene alteration analysis performed for SRCHC. An 85‐year‐old Japanese male presented with a tumor in the left axilla. Biopsy of the axilla nodule demonstrated diffuse proliferation of histiocytoid neoplastic cells and signet‐ring cells in the dermis and subcutis. Immunohistochemistry revealed loss of E‐cadherin expression in these neoplastic cells. Accordingly, SRCHC of the axilla was diagnosed. Genetic analysis using next‐generation sequencing demonstrated missense mutation of PIK3CA (c1633G>A, pGlu545Lys) and no CDH1 gene mutation.SRCHC of the axilla is considered equivalent to a histiocytoid variant of invasive lobular breast carcinoma. The present SRCHC case demonstrated a pathogenic PIK3CA mutation, which is observed in invasive lobular carcinoma. Additional large case studies are required to clarify the clinicopathological features and gene alterations in SRCHC of the axilla.